Inorganic Fullerene-like Nanoparticles and Inorganic Nanotubes (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
The subjects of the presented papers cover a wide range of challenges in the area of inorganic fullerene-like nanoparticles and nanotubes. However, it can include only a few comprehensive experimental and theoretical efforts, stepwise evaluating the rationalization of the synthesis, and elucidation of the stability, mechanical, electronic and adhesive properties of these nanostructures. We believe that this thematic issue can be helpful, not only for an advanced researcher to grasp the latest developments in this field, but also to permit a beginner to gain a deeper insight into the field of inorganic fullerene-like nanoparticles and nanotubes.